THE IMPACT OF COVERT ADVERTISING ON CONSUMER BEHAVIOR - Ruzimuratov Akmal Bakhodirovich (American Journals, 2024)
The analysis of "The Impact of Covert Advertising on Consumer Behavior" is very important nowadays, as consumers are constantly exposed to traditional advertisements and have already become immune to them. Covert advertising, in turn, integrates the same content but in a less intrusive way, allowing the brands that use it to gain more trust from consumers. The relevance of covert advertising is confirmed by several factors.